Effect of electrolyte thickness manipulation on enhancing carbon deposition resistance of methane-fueled solid oxide fuel cell - Ab Rahman, Mazlinda; Othman, Mohd Hafiz Dzarfan; Wibisono, Yusuf; Harun, Zawati; F. Omar, Ahmad F.; Shabri, Hazrul A.; Deraman, Shahirah; Rahman, Mukhlis A.; Jaafar, Juhana; Ismail, Ahmad F. (Wiley, 2020)
Dual-layer hollow fiber (DLHF) micro-tubular solid oxide fuel cell (MT-SOFC) consisting of nickel oxide-yttria-stabilized zirconia (NiO-YSZ) anode/YSZ electrolyte was fabricated via a single-step phase inversion-based co-extrusion/cosintering technique in order to investigate the effect of different electrolyte extrusion rates (1-5 mL min−1 ) at different sintering temperature (1350C, 1400C, and 1450C) under methane (CH4) condition. The DLHF co-sintered at 1450C was chosen as optimum temperature due to the good mechanical strength and gas-tight property. Meanwhile, 18 to 34 μm of electrolyte thickness was achieved when electrolyte extrusion rate increase from 1 to 5 mL min−1 . Power density as high as 0.32 W cm−2 was obtained on the cell with the electrolyte layer of 18 μm in thickness (DLHF1) which is 20% higher than the cell with an electrolyte layer of 34 μm (DLHF5) which was only 0.12 W cm−2 when operated at 850C. However, DLHF1 had suffered cracking formation that originated from anode site which shortened the stability test duration to only 8 hours of survival under 750C. While DLHF5 can operate up to 15 hours but an increase in electrolyte thickness had resulted in higher ohmic area-specific resistance that lowering the power density. Fifty-seven percent reduction in cell performance was observed under methane condition when compared to the cell that performs using hydrogen gas due to the carbon deposition as proven by Raman spectroscopy and carbon, hydrogen, nitrogen, and sulfur analyzer.